An NMR‐based biosensor to measure stereo‐specific methionine sulfoxide reductase (MSR) activities in vitro and in vivo - Sanchez Lopez, Carolina (2020)
Oxidation of protein methionines to methionine-sulfoxides (MetOx) is associated with several age-related diseases. In healthy cells, MetOx is reduced to methionine by two families of conserved methionine sulfoxide reductase enzymes, MSRA and MSRB that specifically target the S- or R-diastereoisomers of methionine-sulfoxides, respectively. To directly interrogate MSRA and MSRB functions in cellular settings, we developed an NMR-based biosensor that we call CarMetOx to simultaneously measure both enzyme activities in single reaction setups. We demonstrate the suitability of our strategy to delineate MSR functions in complex biological environments, including cell lysates and live zebrafish embryos. Thereby, we establish differences in substrate specificities between prokaryotic and eukaryotic MSRs and introduce CarMetOx as a highly sensitive tool for studying therapeutic targets of oxidative stress-related human diseases and redox regulated signaling pathways.